Based On Confined Polymerization: In Situ Synthesis of PANI/PEEK Composite Film in One‐Step. Issue 1 (11th November 2021) - Lin, Ziyu; Cao, Ning; Sun, Zhonghui; Li, Wenying; Sun, Yirong; Zhang, Haibo; Pang, Jinhui; Jiang, Zhenhua
Abstract: Confined polymerization is an effective method for precise synthesis, which can further control the micro‐nano structure inside the composite material. Polyaniline (PANI)‐based composites are usually prepared by blending and original growth methods. However, due to the strong rigidity and hydrogen bonding of PANI, the content of PANI composites is low and easy to agglomerate. Here, based on confined polymerization, it is reported that polyaniline /polyether ether ketone (PANI/PEEK) film with high PANI content is synthesized in situ by a one‐step method. The micro‐nano structure of the two polymers in the confined space is further explored and it is found that PANI grows in the free volume of the PEEK chain, making the arrangement of the PEEK chain more orderly. Under the best experimental conditions, the prepared 16 µm‐PANI/PEEK film has a dielectric constant of 205.4 (dielectric loss 0.401), the 75 µm‐PANI/PEEK film has a conductivity of 3.01×10 −4 S m −1 . The prepared PANI/PEEK composite film can be further used as electronic packaging materials, conductive materials, and other fields, which has potential application prospects in anti‐static, electromagnetic shielding materials, corrosion resistance, and other fields. Abstract : Polyaniline/polyether ether ketone (PANI/PEEK) composite film is successfully synthesized using PEEKt film as a template through confined polymerization. PANI and PEEK are co‐grown in situ by one‐step method, and the micro‐nano structure changes are further investigated. PANI/PEEK film has a significant application effect in high dielectric materials, conductive materials and other fields.